Political economy in the Tribunal del Consulado de Santiago de Chile: the case of Manuel de Salas, 1795–1810. - Santa Cruz, Juan Luis Ossa (Colonial Latin American Review, 2020)
The article examines the life and work of the Chilean letrado Manuel de Salas between the years 1795 and 1810. It adds that salas played a key role in developing a sophisticated program of political and economic reforms based on its eclectic readings of the different European schools of the enlightenment. It notes that it combines an analysis of the role of the consulados in eighteenth-century Spanish America, giving special attention to Chile's merchant guild.